Reasons of students and apprentices to choose a training company in the dual system? - Hoxtell, Annette [Verfasser] (My University, 2019)
"This article sheds light on an understudied aspect of the transition from school to work: the choice of a training company. It presents findings from qualitative interviews with 69 secondary school students and apprentices from the German states of Berlin and Brandenburg, focusing on their reasons to choose a training company in the dual system. What reasons lead students and apprentices to choose a training company? The most common reason is personal impressions, which future apprentices obtain in their initial, personal encounters with a company and its staff. Students and apprentices often consider location, working atmosphere and soundness. Due to this study's regional scope, its findings may not be fully generalisable on a national or international level. However, its findings may instigate further research in countries where people pursuing certain types of apprenticeship training have to apply to companies (e.g. Great Britain, Switzerland and Australia)." (Author's abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; I 2.1.1.6 Berlin; I 2.1.1.2 Brandenburg; Berufsausbildung; Betriebliche Berufsausbildung; Ausbildungsplatzwahl; Betrieb; Einflussfaktor; Berlin; Berlin-Brandenburg